Marketing Research as a Way to Increase Competitiveness of Railway Company and Forecasting of Demand for Transport - Yanovska, Viktoriia; Pylypenko, Olena; Tvoronovych, Viktoriia; Bozhok, Anastasiia (International Journal of Engineering and Technology, 2018)
Justification of management decisions for railway companies, under the conditions of the transport market liberalization, requires the search and collection of reliable information which is related with both the internal and external environment. Alongside, the need to provide competitiveness of the railways involves marketing research. The main objective of this paper is to determine the specific features of applying marketing tools for promotion of competitiveness and formation of the railway companyâ€™s strategy. The dynamics of passenger traffic reflects the competitiveness of types of transport in terms of the ability to provide transport services for a better ratio of â€œprice / qualityâ€. The performed researches confirm the presence of opposite tendencies in the long-distance and suburban connections, as well as specific factors of elasticity of demand for passenger transportation at a price. It is established that for the population (the consumer of transport services) the rate of tariffs for transportation is the determining factor of the attractiveness of the carrier in suburban transportation, and therefore it is the factor of its competitiveness, while the rate of tariffs is not the most significant factor in choosing a carrier in long distance transportation. There are subjective technical parameters of competitiveness which do not fit into the â€œprice / qualityâ€ system among the factors of choosing a carrier. During the choice of transportation, the consumer is guided by his own system of values which is not universal and leaves each transport company its â€œnicheâ€ for operation in the market as well as the opportunity to win its â€œownâ€ consumer. Models of forecasting demand for passenger long-distance and suburban transportation by railway and automobile transport are proposed on the basis of forecast of macrofactors. The using of these models will allow railway and automobile companies to form their development strategies.Â Â